Equine Herpesvirus Type 4 Infection: Seroepidemiology, Pathogenesis and the Effect on Racing Performance - Md Isa, Kamarudin (2002)
Equine rhinopneumonitis is an equine respiratory disease caused by equine herpesvirus type 4 (EHV -4). This study provides the first information on the disease status in Malaysia. Serological survey conducted on 1,023 blood samples, representing 23% of equid population in Malaysia (including Sabah and Sarawak) reveals a moderate seroprevalence rate of 60%. However, the prevalence ranges between 0 and 100%. The state that has 0% prevalence maintained the ponies as a closed herd in contrast the states that have 100% prevalence, which are active in importing equids. Sero-prevalence to EHV-4 varies significantly between states, districts, stables, horse and pony types and age but not affected by upgrading of pony blood through cross breeding. Based on the equid types, thoroughbred racehorse has the highest prevalence of 100%, followed by the warm-blooded horse at 46.8% while pony and pony crosses has the lowest prevalence of 36.9%. Intranasal infection of EHV-4 on serologically negative local yearling ponies results in a disease characterised by clinical signs of nasal discharge and fever. The fever is not typical of the hyperthermia caused by viral infection since the biphasic temperature increment is absent. Transient leukopaenia is absent while the arterial oxygen and carbon dioxide partial pressures are not altered. All the changes reflect the mild nature of the EHV-4 infection. The histological and ultra-structural examinations of the mucosa of the respiratory tract indicated a substantial damage of the upper respiratory tract and tracheal mucosa. Multifocal erosion and extensive accumulation of serous, mucus and dead cells on epithelial surface have been observed. Changes in the nucleus include swelling, nucler lysis, nuclear membrane disintegration and dilation of perinuclei membrane. In the cytoplasm, the changes observed include vacuolar degeneration, mitochondria swelling with disintegrated cristaea and accumulation of fluid in cytocavity. Following intra-nasal inoculation, the infectious virus is rapidly transported to the upper respiratory tract and primary bronchiole. By day 7 post-infection, expression of antigen in sub-mandibular lymph node is markedly reduced as compared to day 3, suggesting a quick elimination of EHV-4 antigen. Successful detection of EHV-4 antigen from the nasal swab samples using nested peR at 24-48 hours post-race provides evidence that racing could reactivate latent infection and increase the risk of pony contracting the disease. The EHV-4 infection is found to have a negative effect on racing performance. Racehorses that are sero-negative had higher chances of improving or maintaining finishing position. The effect is more prominent in pony where seropositive pony is less likely to win the race.